2012
DOI: 10.1037/a0028129
|View full text |Cite
|
Sign up to set email alerts
|

Precision of synesthetic color matching resembles that for recollected colors rather than physical colors.

Abstract: Grapheme-color synesthesia is an atypical condition in which individuals experience sensations of color when reading printed graphemes such as letters and digits. For some grapheme-color synesthetes, seeing a printed grapheme triggers a sensation of color, but hearing the name of a grapheme does not. This dissociation allowed us to compare the precision with which synesthetes are able to match their color experiences triggered by visible graphemes, with the precision of their matches for recalled colors based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…Hence, the current results imply the involvement of phoneme processing even during grapheme processing, suggesting the coexistence of acoustic-phonetic and visual-graphemic influences in synesthesia (Simner et al, 2005; Simner, 2007). The current results are also in line with the recent finding that color experienced by grapheme-color synesthetes when viewing inducing graphemes is perceptually comparable to the color recalled from memory when hearing spoken graphemes (Arnold et al, 2012). These results might bear implications in more general context of language processing suggesting visual graphemes automatically activates phonological representations and auditory phonemes automatically activates visual graphemic information (Berent and Perfetti, 1995; Stone et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the current results imply the involvement of phoneme processing even during grapheme processing, suggesting the coexistence of acoustic-phonetic and visual-graphemic influences in synesthesia (Simner et al, 2005; Simner, 2007). The current results are also in line with the recent finding that color experienced by grapheme-color synesthetes when viewing inducing graphemes is perceptually comparable to the color recalled from memory when hearing spoken graphemes (Arnold et al, 2012). These results might bear implications in more general context of language processing suggesting visual graphemes automatically activates phonological representations and auditory phonemes automatically activates visual graphemic information (Berent and Perfetti, 1995; Stone et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it is plausible that enhanced color working memory subserves superior color recognition memory in this population. Recently, Arnold et al (2012) showed that grapheme–color synesthetes were more precise than controls at recalling the color and luminance of a colored circle using a modifiable color patch. Insofar as participants completed the recollection task only 500 ms after stimulus presentation, this result is indicative of superior color working memory among synesthetes and thereby bolsters the present results.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both may be maintained in a phonological loop, and thus dual-coding benefits would not be expected. Alternatively, it may be that color photisms, which do not affect memory in the same way as sensory experiences (e.g., Arnold et al, 2012), do not confer an auxiliary coding advantage in working memory or short-term memory for graphemes in the same way as concurrent sensory experiences do (see also Mastroberardino et al, 2008; Rothen & Meier, 2010). Further research is needed to discriminate between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a common form of synesthesia, grapheme-color synesthesia, graphemes (i.e., letters, punctuation marks or numbers) evoke percepts of color (Cohen Kadosh et al, 2005; Day, 2005; Simner et al, 2006). The percepts can be quite vivid and are cognitively accessible in the sense that they are verbally reportable and can be used by the synesthete to perform certain perceptual and cognitive tasks ranging from color matching (Arnold, Wegener, Brown, & Mattingley, 2012; Blake, Palmeri, Marois, & Kim, 2005) to visual search (Palmeri, Blake, Marois, Flanery, & Whetsell, 2002; Ramachandran & Hubbard, 2001; Ramachandran & Hubbard, 2001) and facilitate learning and memory (Gibson, Radvansky, Johnson, & McNerney, 2012; Gross, Neargarder, Caldwell-Harris, & Cronin-Golomb, 2011; Rothen, Meier, & Ward, 2012; Watson, Blair, Kozik, Akins, & Enns, 2012). However, past accounts of grapheme-color synesthetes generally suggest that the inverse is not the case.…”
Section: 1 Introductionmentioning
confidence: 99%